Follicular lymphoma in a patient with splenosis: a case report. Issue 3 (October 2020) - Kefeli, Umut; Mehtap, Ozgur; Cakir, Ozgur; Eruyar, Ahmet Tugrul; İsgoren, Serkan; Ucuncu Kefeli, Aysegul
Splenosis refers to the seeding of splenic cells associated with surgery or trauma. Splenosis mimicking other diseases has been reported in the literature. To the best of our knowledge, this is the first case of follicular lymphoma in a patient with splenosis whose diagnosis of lymphoma was delayed because of a known history of splenosis. We report a 48-year-old male patient who underwent splenectomy because of injury from a high fall 20 years previously. He had no symptoms other than mild abdominal pain until 2 years previously, which was thought to be associated with splenosis. When his symptoms began to increase, he had explorative laparotomy for diagnosis, which was later confirmed as follicular lymphoma. Splenosis may delay the diagnosis of other conditions that can be underestimated. Clinicians should be aware of unusual symptoms in patients with splenosis.